2014
DOI: 10.1089/tmj.2014.0033
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Classification of Heartbeats for Automated Real-Time ECG Monitoring

Abstract: This work provides a guide to the systematic design of an intelligent classification system for decision support in Holter ECG monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…They also analyzed the human walking dynamics to estimate the dominating forces and used this knowledge to find the heading direction of the pedestrian. For the application of biological monitoring, Park et al [29] demonstrated a very promising application to classify and monitor heartbeats, while Nandakumar et al [30] monitored sleep apnea using the sensors in smartphones to develop more convenient conditions for gesture recognition [31]. Besides, there are also some other applications.…”
Section: Related Workmentioning
confidence: 99%
“…They also analyzed the human walking dynamics to estimate the dominating forces and used this knowledge to find the heading direction of the pedestrian. For the application of biological monitoring, Park et al [29] demonstrated a very promising application to classify and monitor heartbeats, while Nandakumar et al [30] monitored sleep apnea using the sensors in smartphones to develop more convenient conditions for gesture recognition [31]. Besides, there are also some other applications.…”
Section: Related Workmentioning
confidence: 99%
“…The second study case, [19], present a preemptive approach to hearth disease management. This is based on the thought that any heart condition has multiple symptoms that can go from arrhythmia, pain, fainting or straight a heart attack.…”
Section: Researchmentioning
confidence: 99%
“…The feature extraction techniques can be grouped according to the mathematical models used to assess the P-QRS-T waveform complexity. The widely used approach applies P-QRS-T onset/offset delineation or extraction of QRS patterns within a fixed-length window around the fiducial point to measure morphological features in the time domain, including amplitudes, areas, specific interval durations or magnitudes and angles of the QRS vectors in the vectorcardiographic (VCG) planes [ 2 – 5 , 8 19 ]. Other ECG descriptors rely on QRS frequency components calculated either by discrete Fourier transform (DFT) [ 11 , 18 , 20 ] or by computationally efficient algorithms with filter banks [ 4 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different mathematical approaches for decision support systems have been proposed for the automatic classification of heartbeats. Widely applied classification methods are based on linear programming using the Kth nearest-neighbours (KNN) using clustering technique [ 5 , 9 11 , 26 ], linear discriminant analysis (LDA) [ 3 , 13 15 ], fuzzy analysis [ 4 , 12 , 21 ] and decision tree classifiers [ 7 , 8 , 16 , 17 , 21 , 25 , 32 ]. Another frequently used classifier is the support vector machine (SVM)–least square SVM applying linear kernel function [ 22 – 24 ] or SVM relying on quadratic optimization by mapping of the feature space into a high dimensional space using various kernel transformations like hyperbolic tangent sigmoid transfer function [ 18 ] or Gaussian radial basis function [ 19 , 20 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation